A new burnetiid from the middle Permian of Zambia and a reanalysis of burnetiamorph relationships. (13th January 2021) - Kammerer, Christian F.; Sidor, Christian A.
Abstract: A new taxon of burnetiamorph therapsid, Mobaceras zambeziense gen. et sp. nov., is described on the basis of a partial skull recovered from the lower Madumabisa Mudstone Formation (Guadalupian) of Zambia. This taxon can be distinguished from all previously known burnetiamorphs by its unique cranial boss morphology, including a bulbous nasal boss on a 'stalk' and highly discretized, exaggerated anterior and posterior supraorbital bosses. Burnetiamorph phylogeny has recently become contentious; here, support for conflicting phylogenetic topologies is evaluated on a character‐by‐character basis and a revised phylogenetic analysis is presented. The clades Burnetiamorpha and Burnetiidae are supported with their traditional composition, including genera (viz. Bullacephalus and Pachydectes ) recently assigned to a separate family (Bullacephalidae, here considered synonymous with Burnetiidae). The traditional dichotomy within Burnetiidae into Burnetiinae and Proburnetiinae is upheld, with Mobaceras recovered as a burnetiine, along with Bullacephalus, Burnetia, Niuksenitia, and Pachydectes .